SBA-16-Supported Cobalt Catalyst with High Activity and Stability for FischerâTropsch Synthesis - Zhao, Yanxi; Zhang, Yuhua; Chen, Jian; Li, Jinlin; Liew, Kong Yong; Mohd Ridzuan, Nordin (Wiley-VCH Verlag GmbH & Co KGaA, 2012)
SBA-16 molecular sieves were used as support to prepare cobalt catalyst for FischerâTropsch synthesis (FTS). The catalysts were characterized by using TEM, power XRD, temperature-programmed reduction, and N2 adsorptionâdesorption. The analyses indicate that most of the Co3O4 nanoparticles were introduced into the SBA-16 cages, and the SBA-16 mesostructure was retained after cobalt impregnation. The Co/SBA-16 catalyst exhibited higher cobalt dispersion compared to theCo/SiO2 catalyst. The catalytic properties of the catalysts in FTS were evaluated in a fixed-bed reactor. The effect of the addition of water was measured in a continuously stirred tank reactor. High FTS activity and stability were observed on the SBA-16-supported catalyst. The SBA-16-supported cobalt catalyst shows low mobility of cobalt particles in the SBA-16 cages. Unlike silica, the SBA-16 support can efficiently prevent the aggregation and sintering of cobalt nanoparticles.